Analisis Kemampuan Pemecahan Masalah Matematika Siswa Kelas VII pada Materi Bilangan Pecahan Melalui Pendekatan Metakognitif-Diskursif di SMPK St. Paulus Karuni - Ratu, Meriana; Moza, Florida (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine the mathematical problem solving abilities of class VII students who use the Metacognitive-Discursive approach to fractional number material based on the Polya indicator. The type of research used is qualitative descriptive research. The subjects in this research consisted of 3 students. Data collection techniques in this research used test methods, interviews and documentation of test results. The data analysis technique is: first, students are asked to work on questions. Second, the results of student work are analyzed with the aim of finding out what students’ abilities are in solving problems. Third, from the results of the analysis conclusions are drawn. The results of this research show that each student has a different problem solving process, namely, students in the high category are able to solve mathematical problems through the Polya stages. Students in the medium category have not been able to solve mathematical problems through the Polya stages as a whole. Even though there are several Polya strategies that are not used in the completion step, they can complete it well. Students in the low category tend to be limited to understanding the problem and have not been able to solve mathematical problems through all stages of Polya